Progress in chemical toxicology. - Stolman, Abraham, 1908- (Academic Press, 1974)
Progress in Chemical Toxicology, Volume 5 covers topics on the improved isolation and detection procedures and quantitation methods for volatile poisons, stimulants, hallucinogenic drugs, and marihuana. The book discusses the absorption, distribution, and excretion of drugs and poisons and their metabolites; the system for the toxicological analysis of drugs in biological specimens; and the isolation and analysis of phenothiazines. The text also describes the use of fluorescence in toxicology and the toxicology of new synthetic organic polymers used in containers for food, pharmaceutical compo.